Aplastic anemia after hepatitis - Berkel, İzzet (The Turkish Journal of Pediatrics, 1969)
A case of aplastic anemia following infectious hepatitis is reported. Possibilities for the association of aplastic anemia and hepatitis are discussed and the related literature is briefly reviewed.